141 What makes patients prefer hospital based breathlessness support services compared to GP based services? Qualitative analysis of free text questions within a discrete choice experiment. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Raja, U; Yi, D; Lovell, N; Higginson, IJ
Abstract : Introduction: Chronic breathlessness is common, and is frightening for patients and carers with associated distress and higher care use. The OPTBREATHE study (a discrete choice experience (DCE)) looked at patient and carer preference with regards to breathlessness support services, and found that patients and carers preferred hospital based services when compared to GP based services. Aim: Using free text questions within the DCE, explore possible reasons why patients and carers might express a preference for hospital-based breathlessness support services. Methods: Textual analysis of the free text questions (completed by participants) alongside the DCE as part of the OPTBREATHE study. Free text answers were analysed thematically and grouped into categories. Results: 190 patients and 68 carers participated in the DCE. There were 69 free-text answers provided. Data was organised using the following categories: waiting times, additional support by professionals, presumed quality of care, perceived risks, location of care and patient or carer preferences. There were 5 occurrences of the belief that GPs couldn't provide specialist care. 1 patient did not want to see the GP due to perceived risk of infection. 6 patients didn't want to have any additional support provided by professionals such as social workers and physiotherapists. There were 11 occurrences of patients wanting to have all the treatment at home. Conclusion: Analysis of the free text questions provides some understanding about why patients and carers might express a preference for hospital based breathlessness support services. Educating patients and carers may help change attitudes and increase access to GP-based services in the future. Multiple patients and carers wanted the majority of services to be provided at home. This would need to be thought of including providing care with a healthcare professional they prefer.